PENGARUH MEREK, HARGA, FITUR PRODUK DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE XIOMI DI TOKO CENDANA CELL BANJARNEGARA - Setijadi Setijadi; Wisnu Satria Kencana Wijaya (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2021)
ABSTRACT This study aims to determine how much the brand, price, product features, and lifestyle variables affect the Xioami smartphone purchase decision at Cendana Cell Banjarnegara. The data used in this research were obtained from the results of distributing questionnaires to 154 respondents who used Xioami smartphone users in Cendana Cell Banjarnegara using the Non Probability Sampling method. The research data were analyzed using multiple linear regression analysis, the equation model was processed using SPSS for windows version 2.4. The results of this study are that the brand variable has no significant and negative relationship, followed by the price variable which has no significant effect and has a negative relationship. Meanwhile, product features and lifestyle have a significant and positive effect. Together, brand and price variables do not have a significant effect and are negatively related. Meanwhile, product features and lifestyle influence the decision to purchase Xioami smartphone at Cendana Cell in Banjarnegara.